Sustainability of the Italian Healthcare System and of the presently active hospitals: a methodological proposal for a systematic assessment of humanization of paediatric care and areas - Felicino, T.; Gola, M.; Buffoli, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. In paediatrics, the word “humanization” means to care for the whole patient’s family. It is vital to preserve a balanced relationship between family members to help the healing process for the young sufferer. How do we ensure that all the strategies adopted up to now have positively reached their objectives of humanization?  How then can we measure hospital users’ perception?The purpose of this research project is to identify the main factors that influence users’ opinion about the quality of environment in paediatrics through a qualitative analysis on users’ well-being.  Monitoring the humanization level achieved by hospitals and testing the effectiveness of spaces devoted to host young people, may be considered essential phases in gathering new useful evidences as well as to identify potential emerging guidelines.Methods. Operative measurements were supported by the LpCp-tool, an effective tool that includes a questionnaire-based investigation and a processing software. The tool was then adapted to the specific explored field. The investigation was applied in three hospitals in Lombardy Region (Italy).Results. The most influent factors in users’ perception were the space comfort and the standards of security services. Hospital staff generally had a worse opinion than patients/visitors on all items. Under no circumstances must users’ involvement relevance be overlooked.Conclusions. The research highlights the relevance of the environmental well-being and involvement of users’ in the decision-making processes, as well as the absolute requirement of a multicultural context.